Horizontal legal protection for building owners on the execution of land in a horizontal perspective - Briggita Naomi Hutagalung; FX. Arsin Lukman (The International Journal of Politics and Sociology Research, 2023)
Indonesian land law adheres to the principle of horizontal distribution. The principle of flat settlement refers to the principle that the buildings and plants on the land do not belong to the land. Land rights do not necessarily include ownership of buildings and factories. Legal actions against land do not necessarily include legal actions against buildings and plants. The approach used in this study is an active legal approach, namely the act of acting or enforcing normative legal provisions for every legal event that occurs in society. The results of the discussion are: 1) The legal consequences of the principle of horizontal distribution in law. From the transfer of land rights it can be concluded that the principle of horizontal distribution applies to buying and selling land without building a house. The difference between the legal subject of the land owner and the legal subject of the building owner. 2) Legal protection against the application of the principle of equity in transferring land rights to parties who control land and/or buildings in good faith.